Pancreatic Anastomosis Disruption Seven Years Postpancreaticoduodenectomy - Walid Faraj; Zaki Abou Zahr; Deborah Mukherji; Ahmad Zaghal; Mohamed Khalife (Case Reports in Medicine)
We are reporting a case of a 22 year-old female patient, who underwent a pancreaticoduodenectomy previously for a solid-pseudopapillary neoplasm of the pancreas and was re-admitted seven years later with a pancreatic leak following disruption of the pancreatico-jejunal anastomosis. Exploratory laparotomy revealed a large collection at the level of the pancreatic anastomosis with major disruption of the pancreatico-jejunal anastomosis. The pancreatic stump was refreshed as well as the jejunal site and a duct to mucosa anastomosis was performed. She remains well with a follow up of 18 months.